Brand Image as a Strategic Lever for Mergers and Acquisitions in the Financial Services Sector in South Africa - Asmal, Ridwaan; Moodley, Marlini (International Review of Management and Marketing, 2024)
There were a number of mergers and acquisition (M&A) and hostile take overs in South Africa over the past decade and half. Companies in a M&A are in most instances preoccupied in pursuit of increasing the shareholder value and securing the biggest market share through effective branding. The research objectives of the study were to evaluate the effectiveness of mergers and acquisitions in relation to its image as a brand and to provide recommendations in respect of future merger and acquisition deals for an organisation. The study adopted the quantitative method of research by means of a survey questionnaire and the target population for this study was 310 managers (in the financial services sector) in Kwazulu-Natal. Relevant descriptive and inferential statistics were used to analyse the data collected. The research findings uncovered that from a turnaround perspective in mergers and acquisition deals, brand image should be skilfully and appealingly crafted to generate the desired return on investment. This study contributes to the body of knowledge by revealing that institutions who merge in the financial services sector consolidate their position in the market if brand image is aligned to the institution’s strategy. A fortified brand image results in greater market share.